2018
DOI: 10.1002/bkcs.11586
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ti Doping on the Structural Stability and Enhanced Electrochemical Performance of α‐LiVOPO4

Abstract: Lithium vanadyl phosphate has seven different crystallographic phases. Among them, α-LiVOPO 4 is chosen because of its relatively high energy density and redox voltage of 3.9 V compared to the other phosphates. In this study, Ti 4+ -doped α-LiV 1−x Ti x OPO 4 (x = 0.00, 0.003, 0.005, 0.007, and 0.01) was prepared using a sol-gel method to increase the structure stability and electrochemical performance. The triclinic structure with the space group P-1 was confirmed by X-ray diffraction, Fourier-transform infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…29−32 substituted ε-LiVOPO 4 compared to the unsubstituted sample, while Xiong et al observed a reduction in the charge-transfer resistance for 4% Mn-substituted β-LiVOPO 4 . 29,30 An increased Li-ion diffusivity was observed for Zr-substituted β-LiVOPO 4 . 31 Despite the claimed success of substitution in these studies, the evidence is based only on X-ray photoelectron spectroscopy, which is surface sensitive, or inductively coupled plasma (ICP)-based spectroscopy, which measures all solid phases in the sample including amorphous and impurity phases.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…29−32 substituted ε-LiVOPO 4 compared to the unsubstituted sample, while Xiong et al observed a reduction in the charge-transfer resistance for 4% Mn-substituted β-LiVOPO 4 . 29,30 An increased Li-ion diffusivity was observed for Zr-substituted β-LiVOPO 4 . 31 Despite the claimed success of substitution in these studies, the evidence is based only on X-ray photoelectron spectroscopy, which is surface sensitive, or inductively coupled plasma (ICP)-based spectroscopy, which measures all solid phases in the sample including amorphous and impurity phases.…”
Section: Introductionmentioning
confidence: 95%
“…Common strategies to improve the reaction kinetics and electrochemical stability at high voltages include the use of a conductive additive, surface coating, elemental substitution, and nanosizing. , Among these approaches, aliovalent substitution has been shown to enhance the electrochemical performance of olivine-based phosphate cathodes by producing structural defects which alter their intrinsic properties for faster Li-ion diffusion. Similarly, previous studies have reported improved electrochemical performance for cation-substituted LiVOPO 4 synthesized via a high-temperature solid-state method. Lee and Ryu demonstrated a reduced voltage hysteresis and an improved retention rate for 0.5% Ti-substituted ε-LiVOPO 4 compared to the unsubstituted sample, while Xiong et al observed a reduction in the charge-transfer resistance for 4% Mn-substituted β-LiVOPO 4 . , An increased Li-ion diffusivity was observed for Zr-substituted β-LiVOPO 4 . Despite the claimed success of substitution in these studies, the evidence is based only on X-ray photoelectron spectroscopy, which is surface sensitive, or inductively coupled plasma (ICP)-based spectroscopy, which measures all solid phases in the sample including amorphous and impurity phases.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been several reports on transition-metal substitution into (Li)VOPO 4 , 38–41 they all focus on intercalating only a single Li + ion, with the exception of Wen et al , who showed multi-Li cycling in Mo-substituted ε-VOPO 4 . 38 Additionally, all these studies focus solely on improving either β- or ε-LiVOPO 4 , but not both.…”
Section: Introductionmentioning
confidence: 99%
“…A separate study has also reported the use of Ti-substitution into LiVOPO 4 . 40 However, the study only focused on ε-LiVOPO 4 and did not take into consideration the effects of the large β-LiVOPO 4 impurity present nor the insertion of the second Li + ion to its electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation